2017
DOI: 10.1001/jama.2017.2297
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intensive vs Moderate Alveolar Recruitment Strategies Added to Lung-Protective Ventilation on Postoperative Pulmonary Complications

Abstract: clinicaltrials.gov Identifier: NCT01502332.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
71
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 29 publications
8
71
0
2
Order By: Relevance
“…For patients at high risk for extubation failure, NIV is recommended after extubation as this may significantly reduce the ICU length of stay and mortality [ 73 ]. In some specific scenarios, for patients with high risk of lung collapse (e.g., morbid obesity or in patients after cardiac surgery), direct extubation from CPAP levels ≥ 10 cmH 2 O (or PEEP ≥ 10 cmH 2 O plus low levels of pressure support) has been used with success, resulting in reduced postoperative pulmonary complications [ 74 ].…”
Section: Statementsmentioning
confidence: 99%
“…For patients at high risk for extubation failure, NIV is recommended after extubation as this may significantly reduce the ICU length of stay and mortality [ 73 ]. In some specific scenarios, for patients with high risk of lung collapse (e.g., morbid obesity or in patients after cardiac surgery), direct extubation from CPAP levels ≥ 10 cmH 2 O (or PEEP ≥ 10 cmH 2 O plus low levels of pressure support) has been used with success, resulting in reduced postoperative pulmonary complications [ 74 ].…”
Section: Statementsmentioning
confidence: 99%
“…Unlike studies addressing measures of complete or partial LPV in heart surgery under CPB in adults, 16,17 related studies in children only reported with lung recruitment using peak airway pressure of 40 cm H 2 O with 8 cm H 2 O PEEP 18 and the safety of lung recruitment by using 10 and 15 cm H 2 O PEEP in pediatric patients with severe CHD 19 . In the present study, we tried to use a complete LPVS in infants undergoing CPB surgery for CHD, including LTVV, appropriate PEEP, and PEEP increment during lung recruitment.…”
Section: Discussionmentioning
confidence: 97%
“…However, traditional protective lung ventilation strategies often need to gradually increase PEEP to the level of 20 cm H2O or even higher [6,10], which will obviously affect the circulation and intracranial pressure of patients [13], and may increase airway pressure, reduce cerebral venous reflux and intraoperative operating space, thus limiting its application in patients with craniotomy. In addition, in clinical work, anesthesiologists often use a single PEEP or pulmonary retention mode, ignoring individual differences among patients, thus affecting the effect of protective lung ventilation [1,14,15].…”
Section: Introductionmentioning
confidence: 99%